Imperial Church Building and Church-State Relations, A. D. 313-363 - Armstrong, Gregory Timon (Church history, 1967)
The study of church-state relations in the age of Constantine may be approached in many ways. Imperial church building is one of these avenues of study and interpretation. Lactantius long ago complained of the building mania of Diocletian and other members of the Tetrarchy. Eusebius lauded the churches of Constantine as signal proofs of his magnificence and as the discharge of a sacred debt. Procopius later condemned the extravagance of Justinian's building programs, although without specifically mentioning churches. And many modern writers have taken the churches of Constantine as evidence for both a personal and a public commitment to Christianity. Only a few historians, however, have asked whether there was an overriding plan or purpose to this activity, e.g., Glanville Downey has suggested the likelihood of a plan in the case of Justinian. Thus arises the question, was the construction of churches the instrument or at least the reflection of an imperial policy toward Christianity?